Dual Analysis of N-methyl-2-pyridone-5-carboxamide and N-1-methylnicotinamide in Urine by HPLC with UV Detection. (14th January 2021) - Nguyen, Van Long; Saldanha, Roxanne; Fitzpatrick, Michael
Abstract: N-methyl-2-pyridone-5-carboxamide (2PYr) and N-1-methylnicotinamide (NMN) are metabolites of the water soluble Vitamin B3 (Nicotinamide). Limited methodologies exist for their dual chromatographic analysis in urine samples. In this study, we developed a method for analysis of both 2PYr and NMN by ultraviolet detection. Urine samples were treated to a salting-out assisted liquid/liquid extraction for the extraction of 2PYr and cation exchange for NMN. Both analytes were separated on a Biphenyl 100 × 2.1 mm, 2.6-μm column. The new assay's performance (specifically 2PYr) was compared against the existing testing protocol (based on a previously published method). Linearity for both analytes was above 0.99 ( r 2 ) up to a concentration range of: 1500 μmol/L (2PYr) and 150 μmol/L (NMN). Intra-assay and inter-assay precision of the method was below 8% (coefficient of variation) except at the lower limit of quantification where it was below 20%. Recovery of 2PYr was above 80% and NMN above 90%. A significant positive bias was observed with 2PYr against the existing method. This new method allows for both 2PYr and NMN to be chromatographed and overcomes sample preparation issues in urine 2PYr analysis.